Morphological and molecular characteristics of Geocenamus longus and the first report of G. brevidens from a karst cave (Nematoda: Merliniidae Siddiqi, 1971) - Rybarczyk-Mydłowska, Katarzyna; Sikora, Grzegorz; Kubicz, Magdalena (Zootaxa, 2022)
The taxonomic status of stunt nematodes remains under investigation. Many nematode species belonging to the subfamily Merliniinae still await for more detailed studies, especially for the analyzes on the molecular level. In the presented work, two nematode species belonging to this subfamily were investigated. Characteristics of Geocenamus longus were expanded on the morphological and the rDNA- and mtCOI-derived molecular data. The mitochondrial sequences are for the first time presented for Merliniinae. Additionally, a bisexual population of G. brevidens was reported and characterized from a new, unique underground environment.